Highly Sensitive Phenol Biosensor Utilizing Selected Bacillus Biofilm Through an Electrochemical Method - Ariyanti, Dita; Iswantini, Dyah; Sugita, Purwantiningsih; Nurhidayat, Novik; Effendi, Hefni; Ghozali, Ali Aulia; Kurniawan, Yehezkiel Steven (UI Scholars Hub, 2020)
An eco-friendly phenol biosensor from Bacillus biofilm was prepared and investigated. The biofilm, which produced tyrosinase enzyme, was successfully immobilized on a screen-printed carbon electrode surface. A total of 72 Bacillus isolates were utilized because of their capability to produce tyrosinase enzyme in tyrosine media. Among them, Bacillus isolate code 100 was selected because it produced an adequate amount of tyrosinase enzyme and a high potentiostat current. The response surface methodology was also used to optimize the phenol sensing condition through an electrochemical method. Results showed that the optimum condition was achieved after 6 days on a phosphate buffer solution (pH of 8), with an optical density of 0.33. Furthermore, the limits of detection and quantification were 3.0 and 13 ng/L, respectively. The measurements of precision yielded a relative standard deviation of < 5%, which is remarkable. Although the biosensor material was used for 35 days, the current throughout was still maintained at 90%, indicating that the evaluated biosensor material has the potential to be used for phenol monitoring on environmental samples in the near future.